2019
DOI: 10.1007/s11356-019-06189-5
|View full text |Cite
|
Sign up to set email alerts
|

Trace element accumulation in Salvinia natans from areas of various land use types

Abstract: Salvinia natans meets many criteria for accumulative bioindicators and phytoremediation agents. However, the majority of studies on its bioaccumulation capacity were performed under controlled culture conditions. In the present study, Salvinia natans was investigated in a field study. Plant and water samples were collected from aquatic reservoirs located in areas with various dominant land uses (forested, agricultural, residential and industrial). Contents of 10 trace elements (As, Cd, Co, Cr, Cu, Fe, Mn, Ni, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Dhir et al [ 61 ] observed a higher accumulation rate for Cr, Fe, Ni, Cu, Pb, and Cd than for Co, Zn, and Mn. Polechońska et al reported S. natans as Cu, Fe, Ni, and Zn accumulator and Mn hyperaccumulator, while Reeves and Baker as Cd, Ni, Cu, Co, Pb, Cr, Zn, and Mn hyperaccumulator [ 16 , 62 ]. S. natans showed a considerable capacity to accumulate metals (Fe, Co, Cr, Pb, Cu, Zn, Cd, and Ni) by increasing the initial concentrations from 30 to 50 mg/L, but the tolerance index decreased, suggesting higher toxicity [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dhir et al [ 61 ] observed a higher accumulation rate for Cr, Fe, Ni, Cu, Pb, and Cd than for Co, Zn, and Mn. Polechońska et al reported S. natans as Cu, Fe, Ni, and Zn accumulator and Mn hyperaccumulator, while Reeves and Baker as Cd, Ni, Cu, Co, Pb, Cr, Zn, and Mn hyperaccumulator [ 16 , 62 ]. S. natans showed a considerable capacity to accumulate metals (Fe, Co, Cr, Pb, Cu, Zn, Cd, and Ni) by increasing the initial concentrations from 30 to 50 mg/L, but the tolerance index decreased, suggesting higher toxicity [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Free-floating aquatic plants are ideal for phytoextraction and rhizofiltration, as they are easy to grow and harvest [ 9 ]. The Salviniaceae aquatic species have a remarkable ability to uptake, tolerate and bioaccumulate toxic inorganic pollutants [ 14 , 15 , 16 , 17 ], phosphates [ 18 ], nitrogen [ 19 ], arsenic [ 20 ], and amino groups from aqueous solutions [ 21 ]. Salvinia natans (L.) All.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After selection of a species that shows high accumulation abilities, the bioindicator should be validated based on a direct positive correlation between element concentrations in plants and their environment or differences/gradients between the contents of analyzed elements in plant tissues from sampling sites of different characteristics (Baldantoni et al, 2018; Bellino et al, 2020; Polechońska et al, 2019; Skorbiłowicz et al, 2018). However, accumulation efficiency, metal concentrations in tissues, and hence usefulness in bioindication in natural conditions depend on many factors and local conditions, so few only general patterns emerge from the literature review.…”
Section: Macrophytes Used As Passive Bioindicatorsmentioning
confidence: 99%